2019
DOI: 10.1111/1750-3841.14906
|View full text |Cite
|
Sign up to set email alerts
|

A Mini‐Review on Brewer's Spent Grain Protein: Isolation, Physicochemical Properties, Application of Protein, and Functional Properties of Hydrolysates

Abstract: There is a growing demand in reusing agro-industrial waste to enrich food proteins and develop new protein-related products. Brewer's spent grain (BSG), the byproducts generated from the processing of beer-brewing industry, is rich in abundant protein (26 to 30%) with good physicochemical properties and nutritional benefits. BSG is mainly composed of four proteins including hordein, gluten, globulin, and albumin. The methods for extracting protein from BSG mainly include alkali extraction, ultrasonic-assisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 92 publications
1
49
0
Order By: Relevance
“…Additionally, hydrothermal pretreatment was studied to increase the effectiveness of protein extraction from BSG (Qin et al., 2018). Currently, according to a previous review (Wen et al., 2019), the structural information of BSG protein is needed to be studied in future research.…”
Section: Nutrition and Biological Activity Of Bsgmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, hydrothermal pretreatment was studied to increase the effectiveness of protein extraction from BSG (Qin et al., 2018). Currently, according to a previous review (Wen et al., 2019), the structural information of BSG protein is needed to be studied in future research.…”
Section: Nutrition and Biological Activity Of Bsgmentioning
confidence: 99%
“…The main compounds of BSG protein are hordein, glutelin, globulin, and albumin (Wen et al., 2019). It is reported that BSG noticeably has a similar number of amino acids as barley (Cermeño et al., 2019).…”
Section: Nutrition and Biological Activity Of Bsgmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential amino acids from BSG are methionine, phenylalanine, tryptophan, histidine, and lysine, and the non-essential are serine, alanine, glycine, and proline [9]. A study conducted by Wen et al (2019) revealed the fact that BSG has a similar composition in amino acids as in germinated barley-rich in glutamine/glutamic acid, vanillin, and leucine but with a smaller content of cysteine and methionine [68].…”
Section: Proteins Protein Hydrolysates Bioactive Peptidesmentioning
confidence: 99%